A challenging broad-complex tachycardia. Issue 2 (1st June 2018) - Iyer, Nithin Ramesh; Oomen, Adrianus W G J; Sy, Raymond W
Abstract : A 53-year-old man presented with chest pain, palpitations and presyncope, without history of overt cardiac disease. The patient was alert. His heart rate was 206 beats per minute, and his blood pressure was 100/50 mm Hg. An intravenous bolus of amiodarone 150 mg was administered in the emergency department. His ECGs preamiodarone and postamiodarone are shown in figure 1 . Echocardiography showed low-normal left ventricular systolic function. Question: What should the next diagnostic test be? Referral for electrophysiology study. Referral for urgent coronary angiography. 12-lead ECG with posterior lead placement. Bedside adenosine challenge.